INTERFERON AND RIBAVARIN ASSOCIATED DEPRESSION IN HCV PATIENTS AND ROLE OF SELECTIVE SEROTONIN REUPTAKE INHIBITORS: Depression in HCV Patients - ., Brig Khalid Bashir; Hussain, Chaudhry Altaf; ., Khan Amer (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the frequency and severity of depression associated with antiviral therapy of Hepatitis C Virus (HCV) infection and effect of selective serotonin reuptake Inhibitors (SSRIs) to treat these depressive symptoms.Type of Study: Observational Analytical study.Place of Study and Duration: The study was conducted at Psychiatry, Medicine and Pathology department of Combined Military Hospital Sialkot Pakistan from February 2009 to July 2010.Subjects and Methods: All the patients in this study were suffering from HCV infection and were managed with Interferon (3 m.i.u. s/c thrice weekly) and Cap Ribavirin (400 mg bid) for six months. Patients were assessed by Hospital Anxiety and Depression Scale (HADS) - Urdu Version and Beck’s Depressive Inventory (BDI) Scores after twelve weeks of antiviral therapy. Depressed patients were managed with selective serotonin reuptake inhibitors (SSRIs) for six weeks and again evaluated on HADS & BDI Scores. Response to SSRIs was defined as complete response, partial response and no response.Results: A total of 105 patients were studied out of which 75 were male and 30 were female with mean age 29.4 years. Out of these 54 (51.43%) patients developed depression and this tendency to develop depression was not related with the age and sex of the patients. The mean HADS and BDI scores before and after treatments with SSRIs were compared for significance and it was quite significant. There was not a single patient who did not show response to SSRIs.Conclusion: Depression is frequently associated with antiviral therapy of HCV RNA viraemia with interferon and SSRIs have proved an effective and safe remedy in these patients.